Dosing of colistin – back to basic PK/PD - Bergen, Phillip J. (2011)
The increasing prevalence of multidrug-resistant Gram-negative bacteria worldwide has led to a re-evaluation of the previously discarded antibiotic, colistin. Despite its important role as salvage therapy for otherwise untreatable infections, dosage guidelines for the prodrug colistin methanesulfonate (CMS) are not scientifically based and have led to treatment failure and increased colistin resistance. In this review we summarise the recent progress made in the understanding of the pharmacokinetics of CMS and formed colistin with an emphasis on critically-ill patients. The pharmacodynamics of colistin is also reviewed, with special attention given to the relationship between pharmacokinetics and pharmacodynamics and how the emerging data can be used to inform design of optimal dosage regimens. Recent data suggest the current dosage regimens of CMS are sub-optimal in many critically-ill patients.